Cárie dentária em crianças pré-escolares: conhecendo o problema e buscando soluções - Iane Resende Oliveira de Amorim (2018)
Early childhood caries is related to malnutrition, low weight, obesity, poverty, cultural and ethnic factors, sugar consumption in the baby bottle and sweets between main meals, chronic diseases in early childhood and poor health care assistance. The objective of this study was to identify the prevalence of dental caries and associated factors in children from 3 to 5 years old, as well as to evaluate the perception of health professionals of Primary Care on the importance of including the dentist and nutritionist in Child Care in municipality of Congonhas, Minas Gerais. The present study presents two phases. Phase 1 is a cross-sectional study with a quantitative approach that investigated the prevalence of dental caries and associated factors. This collection was carried out at the Basic Health Units by the Oral Health Teams of the Family Health Strategy of the municipality and included an oral clinical examination and evaluation of the children's BMI, besides the application of socio-demographic and food frequency questionnaires from the children to those responsible. The main results were: the prevalence of dental caries was 41%; children with high frequency of drinks and sugary foods, including soft drink (p = 0.002), powdered juice (p = 0.090) and cookies (p = 0.314) had a higher occurrence of the outcome. There was no association between body mass index (BMI) and dental caries. In the adjusted final model, children cared for by direct and indirect family or neighbors (p = 0.022) had a higher prevalence of dental caries when compared to children cared for by the mothers. Never consuming soda (p = 0.001) and cookies (p = 0.029) was a protective factor for dental caries in children. Phase 2 consisted of a qualitative study, in which a focus group was formed with Primary Care professionals: nurses, doctors, dentists and nutritionists. For the achievement of the focal group a semi-structured guide was used. After the first conversation that aimed at clarifying and relaxing the group, the motivating question was asked "How does the group of child care in this municipality?". Then the guide was explored, in continuity with the established conversation, trying to address the importance of this joint work, what is the role of each one in the group and what could be the participation of the dentist and the nutritionist in this team. It was concluded that the prevalence of dental caries in pre-school children was high and associated with high frequency of consumption of drinks and sugary foods. There is a need for food orientation, emphasizing the influence of diet on obesity and dental caries, as well as focusing on the prevention of common risk factors in public health actions. As technical product was written a book chapter being the target public health professionals; from the qualitative study it is intended to insert into the municipality, in the form of a pilot project, oral health activities in the Child Care Group.